Implementation of Project Based Learning Integrated TPACK in Improve Creative Thinking Skills Through Lesson Study - Edy Waluyo (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
Facing 21st century learning, lecturers need to carry out student-centered learning that is able to improve creative thinking skills. This research aims to improve students' creative thinking skills by applying Project Based learning integrated TPAC through lesson study. This study used classroom action research through study lessons with three open classes with subjects totaling 32 students of the Hamzanwadi University, mathematics education study program. The data were analyzed using descriptive statistics. Student activity scores during the learning process from the first, second and third open classes were 73.34%, 77% and 87% there was an increase in average activity of 6.83%. Data on the percentage of students who scored the ability to think above 75 in the first open class was 78.13%, the second open class was 81.25% and the third open class was 93.75%, there was an average increase of 7.81%. The conclusion of this study is that the application of Project Based learning integrated TPACK through lesson study can improve students' creative thinking skill. Researchers hope that lecturers can apply TPACK integrated project-based learning to the courses taught.